2008
DOI: 10.1097/aco.0b013e32830eb69d
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines as pain mediators and modulators

Abstract: Purpose of review-Chemokines are central to the innate immune response following tissue damage, injury and some diseases. The function of chemokines in nervous system autoimmune diseases has been long recognized. There is also growing evidence that disease-associated of injuryinduced functional expression of chemokines/receptors in both neural and non-neural elements of the peripheral nervous system play crucial roles in the pathophysiology of chronic pain.Recent findings-Chemokine involvement in neuropathic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 58 publications
(54 reference statements)
1
72
0
Order By: Relevance
“…In the last decade, numerous studies have demonstrated that, in addition to their role in coordinating the immune response, chemokines have important functions in the nervous system [6]. For example, excitatory chemokine signaling has been implicated in the pathogenesis of chronic pain in several animal models [7]. Stromal cell-derived factor-1a (SDF-1a), now also named CXCL12, belongs to the CXC subfamily and is a ligand for the G-protein-coupled receptor CXCR4.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, numerous studies have demonstrated that, in addition to their role in coordinating the immune response, chemokines have important functions in the nervous system [6]. For example, excitatory chemokine signaling has been implicated in the pathogenesis of chronic pain in several animal models [7]. Stromal cell-derived factor-1a (SDF-1a), now also named CXCL12, belongs to the CXC subfamily and is a ligand for the G-protein-coupled receptor CXCR4.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, evidence has mounted for bi-directional feedback between immunogenic and neurogenic mechanisms in airway inflammation (6,7). Neuronal activation causes pain and irritation, neurogenic inflammation, mucus secretion, and reflex responses, such as cough, sneezing, and bronchoconstriction (8,9).…”
mentioning
confidence: 99%
“…4 Sensitization may occur peripherally (increased responsiveness of receptors) or centrally (increased responsiveness of secondary neurons in the central nervous system to stimuli that may even be subthreshold). 22,23 The cellular and neurochemical mechanisms underlying hyperalgesia and allodynia are complex and beyond the scope of the current article. The clinical implications of hyperalgesia and allodynia are important, since individuals who develop sensitization are at high risk of progressing from acute to chronic pain.…”
Section: Acute Pain: Progression To Chronic Painmentioning
confidence: 99%
“…13 Acute pain, even of relatively short duration, activates secondary peripheral and central mechanisms that may result in hyperalgesia and allodynia. 22,23 Hyperalgesia is increased sensitivity to pain, and allodynia is a special case of hyperalgesia involving painful sensations caused by stimuli that do not normally elicit pain. 4 The physiological mechanism underlying both hyperalgesia and allodynia is sensitization, including a reduction in pain threshold and increased intensity of response to a previously painful stimulus.…”
Section: Acute Pain: Progression To Chronic Painmentioning
confidence: 99%